2002
DOI: 10.1016/s0896-6273(02)00598-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Shape Representation in Monkey Cortex

Abstract: Using fMRI in anesthetized monkeys, this study investigates how the primate visual system constructs representations of three-dimensional (3D) shape from a variety of cues. Computer-generated 3D objects defined by shading, random dots, texture elements, or silhouettes were presented either statically or dynamically (rotating). Results suggest that 3D shape representations are highly localized, although widely distributed, in occipital, temporal, parietal, and frontal cortices and may involve common brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
117
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 63 publications
(3 reference statements)
12
117
4
Order By: Relevance
“…S1). This finding contrasts with the fMRI data from anesthetized monkeys, which show no 3D-SFM sensitivity to random dot stimuli in V4 (13). Yet our human fMRI results matched the awake monkey fMRI data: A large region of cortex immediately posterior to hMT/V5ϩ was more activated during 3D than during 2D moving displays.…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…S1). This finding contrasts with the fMRI data from anesthetized monkeys, which show no 3D-SFM sensitivity to random dot stimuli in V4 (13). Yet our human fMRI results matched the awake monkey fMRI data: A large region of cortex immediately posterior to hMT/V5ϩ was more activated during 3D than during 2D moving displays.…”
contrasting
confidence: 95%
“…In line with earlier reports (4)(5)(6)13), area MT/V5 was activated more by 3D than by 2D moving random-line displays. In addition, the area in the fundus of the superior temporal sulcus (FST) also exhibited significant 3D-SFM sensitivity (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, it has been shown that using remifentanil (an ultra-fast-acting -opioid receptor agonist) has no significant effect on the neurovascular and neural activity of brain areas that do not belong to the pain matrix (Lund et al, 1994;Logothetis et al, 1999Logothetis et al, , 2009Sereno et al, 2002;Zappe et al, 2008a,b). In particular, visual cortex does not bind remifentanil (Jones et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Details on these applications can be found in various recent publications (Logothetis et al 1999;Rainer et al 2001;Tolias et al 2001;Brewer et al 2002;Sereno et al 2002).…”
Section: Mri Of the Monkey Brainmentioning
confidence: 99%